(3GSFdI hMdhds - (3HTjQ YHGS eMehO(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2009)
(3eaGgje JShjbjI, eHGOF GdJShjb, OQGSGJ JShjbjI eJNUUI, EOGQI GdeHjYGJ, EOGQI GdJQhjL, EOGQI GdJhRjY, GSJQGJjLjGJ GdJShjb, Sdhc GdeSJgdc hGdJSYjQ, GdJShjb GdUfGYj, JShjb GdNOeGJ, GdJShjb GdeUQaj, GdJShjb GdOhdj, EOGQI GdJShjb, GdJShjb GdUjOdGfj, HMhK GdJShjbs
Keywords: (3GOGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdOhdjs